М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
di630
di630
11.05.2021 16:39 •  Алгебра

35.19. 1) (2,3x - 10) (5,29x + 23x + 100) - 125x = 12,167x®; 2) (20 + 1,7x) (2,89x1 - 34x + 400) - 400x = 4,913x";
3) 5(x - 6)- 13(2 + x + 32-8x*(x + 21);
4) -6(4 + x + 3(5 - x - 1017 - 9x'(3 + x).​


35.19. 1) (2,3x - 10) (5,29x + 23x + 100) - 125x = 12,167x®; 2) (20 + 1,7x) (2,89x1 - 34x + 400) - 4

👇
Открыть все ответы
Ответ:
bumnov23
bumnov23
11.05.2021

3) 3/10

4) 4/14

5) 4/5

6) 4/15

7) 26,3

8) 4,5

9) 19,68

10) 1,6

Объяснение:

3) (6/5-3/4) * 2/3 = ((24-15)/20) * 2/3 = 9/20 * 2/3 = 3/10

4) (8/7-1/14+1/42) * 12/46 = ((48-3+1)/42) * 12/46 = 46/42 * 12/46 = 12/42 = 4/14

5) 1  2/5 + 3/8 - 39/40 = 7/5 + 3/8 - 39/40 = (56 + 15 -39)/40 = 32/40 = 4/5

6) (6/5 - 2/3) * 1/2 = ((18-10)/15) * 1/2 = 8/15 * 1/2 = 4/15

7) 6,8 * 3,5 + 2,5 = 23,8 + 2,5 = 26,3

8) 8,26 - 7,52 : 2 = 8,26 - 3,76 = 4,5

9) 4,6 * 3,9 + 1,74 = 17,94 + 1,74 = 19,68

10) 4,51 - 5,82 : 2 = 4,51 - 2,91 = 1,6

В 4) и 5) дроби сокращены.

4,7(1 оценок)
Ответ:
rjdfy
rjdfy
11.05.2021
1)
2ху+3х+2у²+3у=(2ху+2у²)+(3х+3у)=2у(х+у)+3(х+у)=(х+у)(2у+3)
2)
ху-у²-х²+у²=(ху+у²)-(х²-у²)=у(х+у)-(х-у)(х+у)=(х+у)(у-х+у)
3)
2х³-16-х²+4=(2х³-16)-(х²-4)=2(х³-2³)-(х-2)(х+2)=2(х-2)(х²+2х+4)-(х-2)(х+2)=
=(х-2)(2х²+4х+8-х-2)=(х-2)(2х²+3х+6)
4)
х³+8-х²-2х=(х³+8)-(х²+2х)=(х³+2³)-х(х+2)=(х+2)(х²-2х+4)-х(х+2)=
(х+2)(х²-2х+4-х)=(х+2)(х²-3х+4)
5)
х²-4х-(х-4)²=(х²-4х)-(х-4)(х-4)=х(х-4)-(х-4)(х-4)=(х-4)(х-х+4)=(х-4)·4=4(х-4)
6)
2х²у²-3у²-2х³+3х=(2х²у²-2х³)-(3у²-3х)=2х²(у²-х)-3(у²-х)=(у²-х)(2х²-3)
7)
у-4ху-1+16х²=(у-4ху)+(16х²-1)=у(1-4х)+(4х-1)(4х+1)=у(1-4х)-(1-4х)(4х+1)=
=(1-4х)(у-4х-1)
8)
2ху-2у-х²+2х-1=(2ху-2у)-(х²-2х+1)=2у(х-1)-(х-1)²=(х-1)(2у-х+1)
9)
у²-х²-у³+х³=(у²-х²)-(у³-х³)=(у-х)(у+х)-(у-х)(у²+ху+х²)=(у-х)(у+х+у²+ху+х²)
УДАЧИ!
4,4(75 оценок)
Это интересно:
Новые ответы от MOGZ: Алгебра
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ